(3GdQO Ydi cJGH NjQ GdRGOs - (3Bd cGTa GdZWGA, eMeO MSjf Hf Ydj Hf GdQVG Hf ehSi Hf LYaQ, J (B1373 (3g`s ((3eMeO LeGd GdgGTejs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3abO GWdYJ Ydi cJH hQOJ ef HYV CgGdjS (B... (3SeGMI GdEeGe cGTa GdZWGA heYgG cJGH VNe GdMLe LOjO GdWHYs
(3BNQgG (B:s
.. (3haJM CHhGHG ef GdRfObI de jaJMgG MJi GdOgQjhf hGdeYWdhf hgh jOYj Gfg dG jYed EdG HCNHGQ GdCFeI hdG jYed HGdhLhg GdXfjI (B... (3GdMeO ddg QH GdYGdejfs
(3JHUQI GdYfhGf (B:s
(3QSGdI aj GdQO Ydi cJGH NjQ GdRGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/106s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds